Skala Penelitian Variabel Terprovokasi Dengan Melibatkan Responden Petugas Pengamanan Demonstrasi - Erik Saut Hatoguan Hutahaean Hutahaean; Yuarini Wahyu Pertiwi; Tiara Anggita Perdini (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2022)
Police officers from the Mass Control Unit (DALMAS) are a police unit with the task of providing security against demonstrations. The chaotic conditions of the demonstration became a reality that they had to face while on duty. The rioting of the demonstrators not only poses a big risk, but in the rioting there are also efforts that can provoke DALMAS members to become emotional and aggressive, in other words provoked. The provoked variable is a very interesting study, but from the many results of research on aggressive behavior, a measurement scale that can be used to obtain quantitative data has not been found. This study tries to compile constructs and items to be able to measure the state of being provoked. The measurement construct was compiled and tested for conformity by involving 5 assessor panelists, and then 35 members of DALMAS were involved to conduct trials to determine the reliability of the items. The result managed to get a number of items that can be used to measure the state of being provoked, the measurement bits show a fairly accurate reliability. Although the existing items are able to measure variables, these results have not involved a large number of respondents.